A Comprehensive Toolkit for Quick and Easy Visualization of Marker Proteins, Protein–Protein Interactions and Cell Morphology in Marchantia polymorpha - Westermann, Jens; Koebke, Eva; Lentz, Roswitha; Hülskamp, Martin; Boisson-Dernier, Aurélien (Frontiers in Plant Science, 2020)
Even though stable genomic transformation of sporelings and thalli of Marchantia polymorpha is straightforward and efficient, numerous problems can arise during critical phases of the process such as efficient spore production, poor selection capacity of antibiotics or low transformation efficiency. It is therefore also desirable to establish quick methods not relying on stable transgenics to analyze the localization, interactions and functions of proteins of interest. The introduction of foreign DNA into living cells via biolistic mechanisms has been first reported roughly 30 years ago and has been commonly exploited in established plant model species such as Arabidopsis thaliana or Nicotiana benthamiana. Here, we report the fast and reliable transient biolistic transformation of Marchantia thallus epidermal cells using fluorescent protein fusions. We present a catalog of fluorescent markers which can be readily used for tagging of a variety of subcellular compartments. Moreover, we report the functionality of the bimolecular fluorescence complementation (BiFC) in M. polymorpha with the example of the p-body markers MpDCP1/2. Finally, we provide standard staining procedures for live cell imaging in M. polymorpha, applicable to visualize cell boundaries or cellular structures, to complement or support protein localizations and to understand how results gained by transient transformations can be embedded in cell architecture and dynamics. Taken together, we offer a set of easy and quick tools for experiments that aim at understanding subcellular localization, protein–protein interactions and thus functions of proteins of interest in the emerging early diverging land plant model M. polymorpha.